Critical radius phenomenon and mechanism for SF6 gaps under very fast transient and lightning impulse voltages. Issue 3 (19th December 2017) - Zhang, Lu; Wu, Jingfeng; Wang, Sen; Sun, Lei; Zhang, Qiaogen
Abstract : Insulation‐related accidents of gas‐insulated switchgear, induced by very fast transient overvoltage, have become increasingly serious in high‐voltage power systems. A steep‐fronted impulse voltage test equipment is developed for studying the discharge characteristics and mechanisms in the SF6 gap. The influence of the electrode radius on the breakdown characteristic of a fixed‐distance SF6 gap is studied. It is found that discharge behaviors of the SF6 gap show the so‐called critical radius effect. With decreasing electrode radius r, the 50% breakdown voltage of the gap decreases till a critical radius R cr is reached, and then remains practically constant for further reduction of r . R cr increases with decreasing gas pressure and wave front time. Calculation results show that R cr is physically close to the length of the filamentary streamer zone L for negative voltages, whereas for positive voltages, R cr is close to the length of the homogeneous streamer zone l . The critical radius phenomenon is related to the streamer–precursor–leader discharge process in SF6 gas, which is discovered and explained for the first time in this paper by the proposed critical charge criterion of leader breakdown. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.